Hagiography and Religious Truth: Case Studies in the Abrahamic and Dharmic Traditions. Rico G. Mong, Kerry P.C. San Chirico & Rachel J. Smith (eds.). London: Bloomsbury, 2016. P.p. 265. ISBN 978-1-47423577-8. (2018) - Wood, Martin
No abstract available